Bimbingan Kelompok Berbasis Experiential Learning melalui Permainan: Mewujudkan BK yang Menyenangkan - Kurniawan, Maulana Ichsan; Prasetya, Akhmad Fajar; Saputra, Wahyu Nanda Eka; Handaka, Irvan Budhi (Jurnal Ilmu Bimbingan dan Konseling, 2025)
This study discusses the application of experiential learning-based group guidance through games as a strategy to create fun and meaningful Guidance and Counseling (BK) services. Through a literature study of 20 relevant articles, it was found that traditional and educational games are able to build character, increase empathy, reduce aggressive behavior, and encourage students' self-acceptance. This approach is in line with Ki Hajar Dewantara's philosophy which emphasizes active, reflective, and contextual learning. The results of the study show that games are effectively used as a participatory and student-centered BK service medium.